Nonlinear Mixed $λ$-Jordan Triple Derivation on $*$-algebras (European Journal of Pure and Applied Mathematics, 2024)
Let $\mathcal{A}$ be a $*$-algebra with unit $I$ and $P_1$ and $P_2 = I - P_1$ includes a non-trivial projections, and let $λ \in \mathbb{C}\setminus\{0,-1\}$. In this paper, We aim to study the characterization of nonlinear mixed $λ$-Jordan triple derivation on $*$-algebras. As an application, we can also apply our results on prime $*$-algebras, factor von-Neumann algebras and standard operator algebras.
Keywords: $λ$-Mixed Jordan triple derivation; $*$-derivation; $*$- algebra